PROFESSIONALS OF THE XXI CENTURY. CIRCULAR ECONOMY - Sysoiev Oleksii (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article considers the problem of training professionals in a fundamentally new direction for Ukraine, namely professionals in circular economy; reveals the economic essence and meaning of the concept of «circular economy»; historical aspects of its formation are analysed; importance for sustainable development of society, the environment protection, human health. Circular, or closed-loop economy - a model of economic development, the basis of which is the rational use of resources and their recovery; it is based on extending the product life cycle, restoring resources, recycling, switching from fossil fuels to using renewable energy sources. Thus, a regenerative, regenerative and integrated circular economy aims to support sustainable economic development without harming the environment. The article concludes that the implementation of the ideas and principles of the circular economy requires the training of professionals of the new formation with the appropriate level of environmental awareness and understanding of the needs of sustainable development of society. Such specialists must not only have a perfect economic education, but also understand the issues of production, be able to respond quickly to the problems of environmental protection and human health, and have an active civil position. In the leading countries of the world professional training of experts in circular economy is already carried out. It is absent in Ukraine today. Thus, in the conditions of growing consumption, accumulation of mass of waste, which cannot be quickly processed in the natural environment and have a harmful impact on the environment, the problem of professionals training in the circular economy in Ukraine needs an immediate solution.